Escenario y problemática de conservación de los Murciélagos (Chiroptera) cavernícolas del Complejo Volcánico de Colima, Jalisco-Colima, México. - Segura-Trujillo, Cintya Araceli; Navarro-Pérez, Sonia (THERYA, 2010)
Our research was conducted Colima Volcanic Complex (CVC) and was to make a first list of cave-dwelling bats on the basis of bibliographic records and sampling in caves and forests. We found 25 species of which six are new records for the area (Glossophaga morenoi, Hylonycteris underwoodi, Chiroderma salvini, Artibeus hirsutus A. intermedius, and Myotis velifer) also were recorded and described the anthropic disturbances underground roosts in the area inhabited by bats. The roosts found were seven from wich five species are that inhabit. The main disturbances were found demolishment and local tourism, the biggest disturbance roosts were three caves in Apastepetl and the cave Argum. Also included a study of risk categories based on the abundance and local distribution in two forest types area representative. We found 17 species of cave bats found by sampling in: the cloud forest and Abies forest. Seven species were obtained within two main categories. Of which H. underwoodi and A. hirsutus were categorized as locally rare and restricted Key words: Anthropogenic disturbances, Chiroptera, Conservation, Forest, Trans-Mexican volcanic belt, Underground roosts.